Synergistic Removal of Cr(VI) with Stable Nanozerovalent Iron Particles and Ultrasound Assistance in the Presence of Organic Additives - Cancelada, Lucia; Meichtry, Jorge Martin; Destaillats, Hugo; Litter, Marta Irene (American Chemical Society, 2024)
Fil: Cancelada, Lucia. Comisión Nacional de Energía Atómica. Gerencia del Área de Seguridad Nuclear y Ambiente. Gerencia de Química (CAC); Argentina